Pengaruh Kepercayaan dan Ulasan Online terhadap Keputusan Pembelian Kahf Face Wash pada Mahasiswa Universitas Teknologi Digital - Aldy Santo Hegiarto; Salman Anshori (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This paper investigates the simultaneous and partial effects of online testimonials and trust on customer buying decisions for Kahf face wash via Shopee. A quantitative approach with an associative-causal research framework was utilized to conduct the study. The study’s population involved students at Digital Technology University who had purchased Kahf Face Wash products from the Kahf Official Store on Shopee. Data were collected through questionnaires administered to 100 respondents, Data analysis was performed using multiple linear regression, supplemented by t-tests and F-tests to assess significance, alongside the coefficient of determination to measure model fit. The results indicate that trust (0.423; p = 0.017) and digital online testimonials (t = 6.085; p = 0.000) exerted a positive and significant influence on customers buying decisions. Concurrently, both independent variables demonstrated a substantial joint effect (F = 52.948; p = 0.000), explaining 53.2% of the variance in customer buying decisions. These findings suggest that strengthening consumer trust and effectively managing positive online testimonials can enhance consumers' purchasing decisions on digital marketplaces.